Peran Koperasi Dalam Pembangunan Ekonomi Di Desa Bajak II Kabupaten Bengkulu Tengah - Fhikri, Rjialul; Attoriq , Rifki; Putra , Hari Aji Rion Toro (Jurnal Kewirausahaan dan Bisnis, 2022)
The role of cooperatives in economic development in Bajak II Village, Bengkulu Tengah Regency is the focus of this research. Cooperatives have great potential in strengthening the local economy by providing financial services, facilitating the marketing of local products, and providing training and mentoring to their members. This research aims to analyze the contribution of cooperatives in advancing the economic sector at the village level, by examining various aspects such as access to capital, income generation, and micro and small business development. The research methods used include interviews with cooperative members, secondary data collection, and statistical analysis. The results show that cooperatives have a significant role in improving the economic welfare of the people of Bajak II Village, particularly through increasing access to resources and business opportunities. The findings provide a better understanding of the importance of supporting the development of cooperatives as one of the main instruments in local economic development in rural areas.